Improved pharmacokinetics and enhanced efficacy of the vancomycin derivative FU002 using a liposomal nanocarrier - Werner, Julia; Umstätter, Florian; Hertlein, Tobias; Beijer, Barbro; Kleist, Christian; Mühlberg, Eric; Zimmermann, Stefan; Haberkorn, Uwe; Ohlsen, Knut; Fricker, Gert; Mier, Walter; Uhl, Philipp (Nanomedicine. Nanotechnology, biology and medicine, 2024)
Antibiotic resistance still represents a global health concern which diminishes the pool of effective antibiotics. With the vancomycin derivative FU002, we recently reported a highly potent substance active against Gram-positive bacteria with the potential to overcome vancomycin resistance. However, the translation of its excellent antimicrobial activity into clinical efficiency could be hampered by its rapid elimination from the blood stream. To improve its pharmacokinetics, we encapsulated FU002 in PEGylated liposomes. For PEG-liposomal FU002, no relevant cytotoxicity on liver, kidney and red blood cells was observed. Studies in Wistar rats revealed a significantly prolonged blood circulation of the liposomal antibiotic. In microdilution assays it could be demonstrated that encapsulation does not diminish the antimicrobial activity against staphylococci and enterococci. Highlighting its great potency, liposomal FU002 exhibited a superior therapeutic efficacy when compared to the free form in a Galleria mellonella larvae infection model.